(untitled) (Vietnam Journal of Community Medicine, 2022)
Objectives: Recurrent miscarriage is defined as 2 or more consecutive miscarriages before the 22th week of gestation. Early detection of causes of miscarriage can lead better treatment outcomes. Materials and methods: Cross-sectional descriptive study on 52 patients with a history of miscarriage and/or consecutive miscarriage at Nghe An Obstetrics and Pediatrics Hospital from January 2022 to June 2022. Results: Our research has shown that: 30% of pregnant women experienced recurrent pregnancy loss and 88,8% of pregnant women experienced consecutive stillbirth. The prevalence of recurrent pregnancy loss and consecutive stillbirths due to unknown causes accounted for the highest rate of 84.7%. The incidence of successful treatment and treatment failure of threatened miscarriage was relatively 75 % and 25%. The average length of stay for a hospitalization was 18 ± 10,8 days. Conclusions: History of consecutive miscarriage 30%; consecutive stillbirths 88.8%; unknown cause 84.7%. Hospitalization for abdominal pain 40.4%. Treatment success 75%, failure 25%. The hospital stay 18 ± 10.8 days.